Назоваването на най-новите реалности и виртуалности (по примери от киберекологията) - Генев-Пухалева, Илияна (Slavica Lodziensia, 2019)
The paper examines Bulgarian names of concepts (terms or quasi-terms) concerning today’s and future developments of technology, computer systems as well perceptions and experiences related to these technologies and systems. The subject area chosen for analysis is that of cyberecology. The author discusses the neological character of the terms naming new realities and virtualities (including the terms with the formal element cyber-), the structural and semantic features of selected terms while emphasizing the influence of English models. The texts studied in the cyberecological area are considered to be term-generating with a view to their primacy within a new language for specific purposes. Furthermore, attention is drawn to the cognitive syntax (i.e. the ways of introducing new concepts) of the cyberecological texts. The general conclusion of the paper is that the linguistic observation of a sublanguage for specific purposes which is in the on-going process of creation is needed considering that it is important for the future of the Bulgarian language to have Bulgarian names for the future realities.